2005
DOI: 10.1177/106591290505800101
|View full text |Cite
|
Sign up to set email alerts
|

Core Values, Value Conflict, and Citizens’ Ambivalence about Gay Rights

Abstract: Recent research has recognized that many people simultaneously hold positive and negative attitudes about important political issues. In this article, we review the concept of attitudinal ambivalence and propose a survey-based measure of ambivalence adapted from the experimental literature. Extending our earlier work on abortion, analysis of a statewide telephone survey of Florida residents reveals that (1) many people have ambivalent attitudes about issues related to gay and lesbian rights; (2) the amount of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 37 publications
3
69
0
Order By: Relevance
“…However, the findings are suggestive of a problem in contemporary America. Craig et al (2005) noted an increasing ambivalence about gay marriage because of conflicts in core values between the perceived sanctity of marriage and family and the valorization of individualism and personal choice in intimate relationships. We think our findings are consistent with their conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the findings are suggestive of a problem in contemporary America. Craig et al (2005) noted an increasing ambivalence about gay marriage because of conflicts in core values between the perceived sanctity of marriage and family and the valorization of individualism and personal choice in intimate relationships. We think our findings are consistent with their conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Craig, Martinez, Kane, and Gainous (2005) suggest that the growing ambivalence in attitudes, with Americans demonstrating relatively high hostility, negativity, and disapproval about gay marriage, but more positive attitudes toward other gay civil liberties, arises from some basic conflicts over core values. Americans are conflicted over their core values surrounding the perceived sanctity of family and marriage and their own rising individualism and efforts to tailor their life experiences to their personal choice.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Egalitarianism (or supporting equality) in general has been found to be linked with support for policies involving gay rights (Brewer , ; Loftus ), while concern with morality (as well as tradition and family) has been linked with opposition (Brewer , ; Brewer and Wilcox ; Craig et al . ; Gaines and Garand ; Wilcox and Wolpert , ). Reconciling these potentially conflicting core values proves challenging for many Americans.…”
Section: Core Values Media Framing and Implications Over Timementioning
confidence: 99%
“…Research has revealed decreasing hostility (compared with that of previous decades) in America toward homosexuality and gay rights movements (Brewer ; Craig et al . ). Hand‐in‐hand with this, as Wilcox and Wolpert () describe, has come a gradual increase in public support for many policy questions directly and positively affecting gay and lesbian communities.…”
mentioning
confidence: 97%
“…Yet many pro‐choice and pro‐life supporters express some level of ambivalence concerning abortion rights under certain circumstances (Craig, Kane, and Martinez 2002). Moreover, there is accumulating evidence that some citizens are ambivalent concerning other supposedly “easy” targets, including the IRS (Alvarez and Brehm 1998), gay rights (Craig et al. 2005), social welfare (Gainous 2008), political parties (Greene 2005; Pinard 2005), political institutions (McGraw and Bartels 2005), and America itself (Citrin and Luks 2005).…”
Section: Conceptualizing and Measuring Ambivalencementioning
confidence: 99%